2018
DOI: 10.2478/cer-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Remittances on Poverty Alleviation in Selected Emerging Markets

Abstract: The study explored the impact of remittances on poverty in selected emerging markets. On the theoretical front, the optimistic view argued that remittances inflow into the labour exporting country reduces poverty whereas the pessimistic view proponents said that remittances dependence syndrome retards both economic growth and income per capita. Separately, using two measures of poverty [the poverty headcount ratio at US $1.90 and US $3.10 a day (% of population)] as dependent variables, the fixed effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The results presented in Table 3, Panel A and Panel B, show that remittance has a negative impact on poverty in the short run and in the long run under Model 2 when infant mortality rate is used as a proxy of poverty (Pov2). These results are in line with findings from previous studies (see, Adam and Page 2005;Gupta et al, 2009;Anyanwu and Erhijakpan 2010;Nahar and Arshad 2017;Vacaflores 2018;Tsaurai 2018). The…”
Section: Cointegration Testsupporting
confidence: 93%
See 1 more Smart Citation
“…The results presented in Table 3, Panel A and Panel B, show that remittance has a negative impact on poverty in the short run and in the long run under Model 2 when infant mortality rate is used as a proxy of poverty (Pov2). These results are in line with findings from previous studies (see, Adam and Page 2005;Gupta et al, 2009;Anyanwu and Erhijakpan 2010;Nahar and Arshad 2017;Vacaflores 2018;Tsaurai 2018). The…”
Section: Cointegration Testsupporting
confidence: 93%
“…In the study, remittance was found to mitigate poverty. Tsaurai (2018), in a separate study on selected emerging market economies, found remittance to reduce poverty. Azam et al (2016) investigated the impact of remittance on poverty reduction in 39 lower-middle, upper-middle and high-income countries employing panel data.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Studies on the impact of remittances on poverty are also split between those that found a positive impact (Adam Jr. and Page 2005; Gupta et al . 2009; Tsaurai 2018; Musakwa and Odhiambo 2019) and those that found the relationship to be sensitive depending on the poverty proxy used (Azam et al . 2016; Wangle and Devkota 2018).…”
Section: A Review Of Related Literaturementioning
confidence: 99%
“…Thus, the correlations between remittances, population migration, poverty and economic growth from the macro and microeconomic perspective were analyzed for 68 developing countries, and the period 1990-2010, the authors considering that remittances increase with increasing emigration, having a positive effect on poverty reduction, but the impact of remittances on economic growth is difficult to quantify [23]. The impact of remittances on poverty has been analyzed for six emerging countries over the period 1994-2014, using two scenarios; a pessimistic one, where remittances negatively affect both economic growth and per capita income, and an optimistic one in which the remittance flow contributes to the reduction of poverty, the conclusion being the need to establish critical points that remittances have to overcome in order to reduce poverty in labor-exporting countries [24].…”
Section: Methodsmentioning
confidence: 99%